Life History and Population Dynamics of Green Crabs (Carcinus maenas) - Young, Alan M.; Elliott, James A. (Fishes, 2020)
Carcinus maenas (the “shore crab” or “European green crab”) is a very proficient invader (considered to be one of the world’s 100 worst invaders by the IUCN) due to its phenotypic plasticity, wide temperature and salinity tolerance, and an extensive omnivorous diet. Native to Atlantic Europe, it has established two well-studied nonindigenous populations in the northwestern Atlantic and northeastern Pacific and less-studied populations in Australia, Argentina and South Africa. Green crabs are eurythermal and euryhaline as adults, but they are limited to temperate coastlines due to more restrictive temperature requirements for breeding and larval development. They cannot tolerate wave-swept open shores so are found in wave-protected sheltered bays, estuaries and harbors. Carcinus maenas has been the subject of numerous papers, with over 1000 published in the past decade. This review provides an up-to-date account of the current published information on the life history and population dynamics of this very important species, including genetic differentiation, habitat preferences, physical parameter tolerances, reproduction and larval development, sizes of crabs, densities of populations, sex ratios, ecosystem dynamics and ecological impacts in the various established global populations of green crabs.